A highly selective and active metal-free catalyst for ammonia production. Issue 8 (15th July 2020) - Xing, Chengyu; Wu, Chenyu; Xue, Yurui; Zhao, Yingjie; Hui, Lan; Yu, Huidi; Liu, Yuxin; Pan, Qingyan; Fang, Yan; Zhang, Chao; Zhang, Danyan; Chen, Xi; et al.
Abstract : Crystalline fluorographdiyne (cFGDY) is synthesized for ammonia production from nitrogen and water at ambient conditions with 100% selectivity and high-activity. Abstract : We report a facile surface-induced method for the in situ growth of single-/few-layered crystalline fluorographdiyne film on the surface of carbon fibers (cFGDY). The crystallized structure of cFGDY was directly confirmed by the scanning/transmission electron microscopy (SEM/TEM), high-resolution TEM (HRTEM) and computer simulation, selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. cFGDY showed a 9-fold stacking mode. Our results show that cFGDY is a metal-free electrocatalyst with unique structure and excellent performance for ammonia production from nitrogen and water efficiently at room temperature and ambient pressure, achieving a high NH3 production rate and Faraday efficiency in neutral conditions. This work provides an efficient catalyst system with determined chemical and electronic structures for highly selective and active nitrogen reduction, serving as a promising platform towards the development of novel metal-free catalysts.